Aerodynamics of knuckling effect shot using kick-robot - Hong, S.; Asa, T. (International Journal of Applied Sports Sciences, 2011)
The purpose of this study was to discuss the fluid mechanics acting on a non-spinning and low-spinning flight soccer ball, which called Knuckling effect ball or Knuckleball, using the kick-robot. This robot is driven by high-pressure air in an air cylinder up to 500 kPa, being capable of generating a ball flight up to about 30 m/s. The machine with a size of 1.8 m x 2.5 m x 2.0 m in height can be moved, and be set both inside of a gymnasium and outdoor field. The ball speed can be set between 10 m/s and 30 m/s. Some condition of ball hitting can be adjusted, such as the hitting speed for the ball flight speed, the contact angle between the hitting-board and a ball for the shot angle and the off-axis distance between the normal line to the hitting board and the ball center for the ball spin rate. It is planned to conduct experiments on the knuckle effect of a non- or low-spinning soccer ball. It was determined that the peak of the irregular force in this experiment was about 2.1 N (s.d.=0.4 N). Furthermore, the knuckleball was observed to have an average lift force frequency of approximately 2.0 Hz. It can be concluded that the emergence of irregular forces is one of the characteristics of knuckle balls in soccer.